Characteristics Analysis of Dual Bell Nozzle using Computational Fluid Dynamics - Yeasir Mohammad Akib; Asif Kabir; Mahdi Hasan (International Journal of Engineering Materials and Manufacture, 2019)
Space exploration and space tourism have now become a raging competition among the developed nations. For this reason, different types of advanced rocket nozzles with prospective privileges are introduced. Altitude adaptive dual bell nozzle will soon replace the conventional nozzles for the first stage rocket launcher. Indeed, this nozzle has auto adaption capability based on altitude. The major feature of a dual bell nozzle is the two bell-shaped contours separated by an inflection point. This nozzle has left rooms for researchers to test different flight conditions and transition characteristics. In this paper, a dual bell nozzle contour has been developed in MATLAB and analysed for different thermodynamic parameters. ANSYS Fluent is used in analysing flow through the nozzle. Shadowgraph imaging technique is used for measuring density gradient and compared it with fluent results. The simulations were performed by using the k-epsilon turbulence model.